2017
DOI: 10.4172/2327-4972.1000219
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Depression among Qatari Adolescents in Secondary Schools

Abstract: Adolescence is an important period for the development of a socially integrated self-negative, which may affect future decisions through depression and anxiety. It is estimated that 20% of adolescents have some type of psychological disorder, and the most common disorder is depression [1]. Methodology:A cross sectional descriptive study conducted among Qatari adolescents in secondary Schools in Qatar. Multistage sampling technique was applied, 823qatari adolescent students were approached of which 797 agreed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Studies have been done to show relationship between some named factors and depression in adolescents and secondary school students. These factors include Gender: This was among the most significant predictors of depression in a study done by Al-Kaabi et al [14] as it has been found that females were more likely to have depression than males and this comes in agreement with many studies and the fact that females are more susceptible to depression may be explained by the theory that the biological and physical makeup of females automatically puts them more at risk of developing depression, as from puberty onwards, fluctuating hormone levels affects their body both physically and emotionally. [15,16] In addition to biological factors, psychological factors may play a substantial role in the predisposition of females to depression.…”
Section: Prevalencementioning
confidence: 98%
See 1 more Smart Citation
“…Studies have been done to show relationship between some named factors and depression in adolescents and secondary school students. These factors include Gender: This was among the most significant predictors of depression in a study done by Al-Kaabi et al [14] as it has been found that females were more likely to have depression than males and this comes in agreement with many studies and the fact that females are more susceptible to depression may be explained by the theory that the biological and physical makeup of females automatically puts them more at risk of developing depression, as from puberty onwards, fluctuating hormone levels affects their body both physically and emotionally. [15,16] In addition to biological factors, psychological factors may play a substantial role in the predisposition of females to depression.…”
Section: Prevalencementioning
confidence: 98%
“…They also tend to be more affected by the environment around them, and strive for perfection both physically and otherwise. [14] This predefined social role, both increases the pressure, which they place on themselves to please others and increases the likelihood that they will be subjected to some form of abuse during their lifetime [14] hence increasing the likelihood of the occurrence of depression in this gender.…”
Section: Prevalencementioning
confidence: 99%
“…The prevalence of depression among Qatari adults is 13.5% [ 36 ], which is comparable to other developed countries in the region. However, the prevalence of depression among adolescents attending secondary school is alarmingly 34.5% [ 37 ], while depression among university students in Qatar was nearly three times higher than the students in the United States (32% vs. 12.8%, respectively) [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current literature reported as on average about 1 in 20 people are affected by depression which often starts at a young age; impairing functionality, and recurring (Erskine et al , 2017). Trinidad is the larger and more populous of the two major islands of Trinidad and Tobago, (25.3%), in Iran, (43.89), in India school going adolescents 49.2% (Jha et al , 2017; Maharaj et al , 2008; Sajjadi et al , 2013), and in Africa, there are limited studies done among adolescents which show different rates of depression in Kenya (26.4%), Egypt (34.5%), Uganda (21%) and Ethiopia (36.5%) (Al-Kaabi et al , 2017; Khasakhala et al , 2012; Kinyanda et al 2013; Tirfeneh and Srahbzu, 2019).…”
Section: Introductionmentioning
confidence: 99%